Saudi Arabia : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2022)
Saudi Arabia is recovering strongly from the pandemic-induced recession. Higher oil prices provide an opportunity for accelerating further the strong reform drive brought about under Vision 2030.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Saudi Arabia